Structural and mechanistic insights into polymyxin resistance mediated by EptC originating from Escherichia coli. (22nd December 2018) - Zhao, Yanqun; Meng, Qiang; Lai, Yujie; Wang, Li; Zhou, Dan; Dou, Chao; Gu, Yijun; Nie, Chunlai; Wei, Yuquan; Cheng, Wei
Abstract : Gram‐negative bacteria defend against the toxicity of polymyxins by modifying their outer membrane lipopolysaccharide (LPS). This modification mainly occurs through the addition of cationic molecules such as phosphoethanolamine (PEA). EcEptC is a PEA transferase from Escherichia coli ( E. coli ). However, unlike its homologs CjEptC ( Campylobacter jejuni ) and MCR‐1, EcEptC is unable to mediate polymyxin resistance when overexpressed in E. coli . Here, we report crystal structures of the C‐terminal putative catalytic domain (EcEptCΔN, 205–577 aa) of EcEptC in apo and Zn 2+ ‐bound states at 2.10 and 2.60 Å, respectively. EcEptCΔN is arranged into an α‐β‐α fold and equipped with the zinc ion in a conserved mode. Coupled with isothermal titration calorimetry (ITC) data, we provide insights into the mechanism by which EcEptC recognizes Zn 2+ . Furthermore, structure comparison analysis indicated that disulfide bonds, which play a key role in polymyxin resistance, were absent in EcEptCΔN. Supported by structural and biochemical evidence, we reveal mechanistic implications for disulfide bonds in PEA transferase‐mediated polymyxin resistance. Significantly, because the structural effects exhibited by disulfide bonds are absent in EcEptC, it is impossible for this protein to participate in polymyxin resistance in E. coli . Database: Structural data are available in the PDB under the accession numbers6A82 and6A83 . Enzyme: EC 2.7.8.43 Abstract : EcEptC is a phosphoethanolamine (PEA) transferase from Escherichia coli that is unable to mediate polymyxin resistance. Here, we report the crystal structures of the C‐terminal catalytic domain of the protein and demonstrate that it lacks disulfide bonds that are essential in polymyxin resistance. This feature distinguishes EcEptC from CjEptC ( Campylobacter jejuni ) and other PEA transferases and sheds light on the underlying mechanism.